Faktor Integratif Nyama Bali-Nyama Selam: Model Kerukunan Masyarakat pada Era Otonomi Daerah di Bali - I Made Pageh; Wayan Sugiartha; Ketut Sedana Artha (Jurnal Kajian Bali (Journal of Bali Studies), 2013)
AbstractIn some areas in Bali such as Pegayaman a Village (North Bali) and Kepaon Village (South Bali), there are enclave of Muslims community who have long lived in harmony with the Balinese Hindu community. Their presence is based on a long history even from pre-colonial Bali. These two ethnics with different religious background consider themselves relative as can be seen from the integrative expressions of nyama selam (Muslim family) and nyama Bali (Balinese family). The former termused by Balinese to honor Muslim, the later used by Muslim to honor Balinese Hindu. They also share similar traditional practices like ‘ngejot’, giving food/meal to neighbours duringa religious celebration. This article discusses the integrative factors that make the relationship between Muslim and Balinese Hindu in some areas in Bali coexist harmoniously. This integrative factors identified to then be developed and disseminated as guidance to retain harmony or to prevent conflict.